3l+9-l-6=

Simple and best practice solution for 3l+9-l-6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3l+9-l-6= equation:


Simplifying
3l + 9 + -1l + -6 = 0

Reorder the terms:
9 + -6 + 3l + -1l = 0

Combine like terms: 9 + -6 = 3
3 + 3l + -1l = 0

Combine like terms: 3l + -1l = 2l
3 + 2l = 0

Solving
3 + 2l = 0

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 2l = 0 + -3

Combine like terms: 3 + -3 = 0
0 + 2l = 0 + -3
2l = 0 + -3

Combine like terms: 0 + -3 = -3
2l = -3

Divide each side by '2'.
l = -1.5

Simplifying
l = -1.5

See similar equations:

| 4+.14x=5 | | 9y+3=3y+9 | | 4k-9=-3(k+7) | | 12r-(r-7)+6=3(r+6)+8r | | x+3x-2x-2=13 | | 9y+9=3y+9 | | 3k^2=10k-3 | | 8x+5=35+5x | | 42=6x+4-x+13 | | 3t+5=3*5+t | | 10-6p+5p-4= | | 5+2(n+1)=2h | | -4(2t-t)+5t=4t-2 | | 3(5x-7)-12x=-9 | | 6x-10=-8+8x | | x(a-b)=d+c | | 200=n+6(8+3n) | | -3/8x-4=1/8x-5 | | D=Ty | | 6*5+3=y | | 5g-2h=-5 | | 3x+9=7x-5 | | 122=9/5c+32 | | 4w+12(w-1)=36 | | 2(x+5)+3(x-5)=180 | | -5b=-8 | | 4x^2+8x=320 | | 21d-4=-67 | | -5(2t-3)+2t=8t-6 | | 8-2x+8+1=5x+5+1 | | 3*x-4=11 | | 3(4y-21)=7 |

Equations solver categories